Information System Security Analysis at PT. TELKOM Using KAMI Index - SY., Yuliani; Heryono, Heri; Rosita, Ai; Surtia Zulpratita, Ulil; Angga Laksana, Eka; Sulianta, Feri (International Journal of Psychosocial Rehabilitation, 2020)
With the development of information technology, it provides a convenient way for every individual or institution to perform its duties and functions. Information security used by institutions must be maintained, yet they can manage and further avoid failure. Therefore, it is important to assess the relevant institutions to determine the level of maturity and completeness of information security. The assessment carried out was by using the Information Security Index (KAMI) issued by the Ministry of Communication and Information that has fulfilled the requirements and aspects of information security that refer to ISO 27001. Currently, PT Telekomunikasi Indonesia (TELKOM) has implemented information technology. At PT TELKOM, there are well-implemented access controls, including security or supervision of important work locations (server rooms, archive spaces); only employees are given a username and password to access them, and we also have implemented security to detect and prevent network access usage (including network wireless).